An analytical drain current model for undoped GSDG MOSFETs including interfacial hot-carrier effects - Fayçal Djeffal; Toufik Bentrcia; T. Bendib (Physica Status Solidi (C) Solid State Physics, 2011)
In the present work, a comprehensive drain current model including the interfacial hot-carrier degradation effects for undoped symmetric gate stack double gate (GSDG) MOSFET and the expressions of transconductance and drain conductance have been obtained. Exploiting this new device model, we have found that the incorporation of a high-k layer between oxide region and gate metal leads to drain current enhancement, improved output conductance, increased transconductance parameter and enhanced interfacial hot-carrier immunity. The proposed model has been validated by comparing the analytical I-V characteristics with 2-D numerical results. The obtained results may provide a theoretical basis and physical insights for multigate MOSFET-based circuits design including the hot-carrier degradation effects. (© 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)